O processo de patrimonialização e a turistificação da Romaria de Nossa Senhora Medianeira de Todas as Graças de Santa Maria /RS (2003/2012) - Cassol, Francielle Moreira (2014)
Devotion to Our Lady Mediatrix of All Graces began in Belgium in the 1920s, with Cardinal José Desiderio Mercier, one of the pioneers of the theory of mediation, in which Mary is venerated as Mediatrix of Divine grace. In Brazil, the belief in 'Mother Mediatrix' expanded from his devotion in the state of Rio Grande of the South, more specifically from the city of Santa Maria. Today, the festival in honor of Our Lady Mediatrix of All Graces takes place on the second Sunday of November and attracts more than 250,000 people per year, and it still the patron state. This text has among its purpose systematically expound on the history of the Pilgrimage, reflect on the patrimony of the Pilgrimage, as well as analyzing in particular the power relations that transform a religious event in a "merchandise" for local tourism. This research falls within the field of Cultural History and Social Memory, and research in the area of History and participant Line Culture and Heritage Research. In this context, it still aims to discuss and reflect on the processes of construction of social identity of a group of people from the pilgrimages of devotion to Our Lady Mediatrix of All Graces, sometimes advocated as Intangible Heritage. In this context, the methodology consisted of literature review, but mainly in research local primary sources, especially newspapers Reason (1934) and Diary of St. Maria (2002), in a time frame that begins before emergence of devotion, ie, in the late nineteenth century to the present day, with special focus on the last decade of this century. The theoretical framework covered nonacademic local researchers such as Isaiah, Belmonte, Passion, and academics as Weinzemenn Biasoli, Boreli, Borin, Bourdieu, Chartier, Geertz, Pohl and Segalen